A study of fat interesterification parameters’ effect on the catalytic reaction activity of potassium glycerate - Sytnik, Natalia; Demidov, Igor; Kunitsa, Ekaterina; Mazaeva, Viktoria; Chumak, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
The study has disclosed the peculiarities of the interesterification process in the presence of potassium glycerate as the catalyst. The properties of palm olein as a result of interesterification have been found to depend on such parameters as temperature, duration, and catalyst concentration. The study makes use of a central composite design (CCD) of the second order orthogonal plan. The melting temperature of palm olein is accepted as a response function. The initial palm olein and the samples obtained according to the plan of the experiment were researched by differential scanning calorimetry to determine the characteristics of the phase transitions – melting and crystallization. The biggest difference was observed between the melting temperatures in a capillary and the temperature peaks on the curves of DSC thermograms for highlyfusible samples; the peak temperature in the DSC thermogram exceeds in these cases the temperature determined in the capillary. The study has revealed that the maximum melting temperature of palm olein occurs during the interesterification process at a temperature of 100 °C, with the process duration of 1.5 hours, and with the catalyst concentration of 0.5 %. The temperature difference between the initial melting and the interesterified palm olein was observed as exceeding 12 °C when the catalyst concentration, most often used in interesterification, was 0.1 %, at a temperature of 100 °C, and with the process duration of 1.5 hours.